Biosorption of lead using immobilized Aeromonas hydrophila biomass in up flow column system: Factorial design for process optimization - Hasan S.H.; Srivastava P.; Talat M. (My University, 2025)
Free and immobilized biomass of Aeromonas hydrophila has been utilized for the removal of Pb(II) from aqueous solution. Fitness of Langmuir sorption model to the sorption data indicated the sorption was monolayer and uptake capacity of biomass was 163.9 and 138.88mg/g for the free and immobilized biomass respectively. 85.38% Pb(II) removal was achieved at bed height of 19cm and flow rate of 2mL/min and BDST model was in a good agreement with the experimental results (r2>0.997). An attempt has been made to optimize the process conditions for the maximum removal using Central Composite Design with the help of Minitab® 15 software and the result predicted by optimization plots was 88.27% which is close to the experimental data i.e. 85.38%. Sorption-desorption studies revealed that polysulfone immobilized biomass could reused up to 16 cycles and bed was completely exhaust after 33 cycles. © 2009 Elsevier B.V.